Learning Outcomes Evaluation Through Learning Analytics Systems in Higher Education: A Systematic Literature Review - Mónica Hernández-Campos; Antonio Gonzalez-Torres; Francisco José García-Peñalvo (SAGE Open)
Learning analytics is pivotal for supporting learning, with recent research shifting from concepts to reviews. However, understanding factors influencing learning outcomes in higher education through analytics systems remains underexplored. This study aims to fill this gap, providing a holistic view of factors affecting learning outcomes in higher education through a systematic literature review. The goal is to unravel the intricate connections among factors, learning environments, research scopes, and theory. The search yielded 1,662 results, with 27 studies selected. “Engagement” emerged as the most prevalent factor, followed by “platform behavior,” while “demographic features” and “self-assessment” were least prevalent. Most research focused on learning outcomes as final grades, lacking a consistent theoretical definition. Studies were mainly conducted in virtual and blended learning environments, spanning multiple courses or focusing on a single course. Despite extensive research on learning behavior and engagement in learning management systems, prevalence does not necessarily indicate a comprehensive understanding of factors influencing learning outcomes. This implies a potential gap in information gathering or analysis for deeper insights. Moreover, the lack of a consistent theoretical framework and the restriction of analyses to final or partial grades in virtual or blended learning environments suggest areas for improvement in learning analytics research. The study proposes directions for enhancing research in this field to unlock its full potential.